Algorithmic-Adaptive Islamic Communication Strategy: Building Hybrid and Ideological Resilience through Palestinian Solidarity Narratives - Mohammad Rofiq; Samsuriyanto Samsuriyanto (Jurnal Ragam Pengabdian, 2026)
The rapid evolution of AI-driven algorithms has decentralized religious authority, leaving moderate Islamic narratives vulnerable to digital extremism and censorship. This study addresses the primary problem of modeling an Islamically- grounded communication strategy adaptive to algorithms to build ideological resilience and Palestinian solidarity. Using the Integrative Synthesis method, this research reconciles normative principles with digital platform logic. Scientific findings, structured into six operational taxonomies and four strategic models— Systemic-Integrated, Alternative Narratives, Hybrid Authority, and Algorithmic Literacy—formulate a “Hybrid Authority” model and an “Algorithmic-Adaptive” framework. This framework synthesizes Islamic ethics, specifically ḥikmah and wasathiyyah, with modern technical competence. This study concludes that media sovereignty for the ummah is achieved by transforming from objects to subjects of algorithms. By integrating technological mastery with prophetic communication, Muslims can effectively neutralize digital radicalization and sustain global advocacy for international justice, ensuring that moderate identities remain resilient and dominant within the competitive digital public sphere.